Application of Chitosan as Chlorine Substitution in Tilapia Fillet (Oreochromis sp.) - Laode Muhamad Hazairin Nadia; Frets Jonas Rieuwpassa; Agustina Agustina; Reni Tri Cahyani; Wulandari Wulandari (Universitas Sriwijaya, 2022)
Chitosan has gained high interest in recent times to extend the shelf-life of fish product due to its nontoxicity, biodegradability, biocompatible and antibacterial activity. This research was aimed to determine the antibacterial effect of chitosan on the shelf-life of tilapia fillets at room temperature storage (25-27 oC). This study used a actorial randomized design (RAF) with two factors, namely antibacterial treatment consisting of 3 levels (positive control with distilled water immersion on tilapia fillets, immersion of tilapia fillets with 0.8% chitosan and negative control with 10 ppm chlorine immersion in tilapia fillet) and observation time consisted of 3 levels (0 hours, 6 hours and 12 hours observations). Antibacterial treatment consisted of 3 levels, namely. Each treatment was carried out in three replications. The data were analyzed using analysis of variance (ANOVA) and the duncan multiple range test (DMRT) at a 95% confidence level. The results of the research showed that chitosan was able to suppress bacterial growth and suppress the increase in TVB values at room temperature storage for 12 hours, indicated by the significant difference in the total number of bacteria and TVB values with chlorine and controls (p<0.05). These indicated that chitosan has a function as a natural antibacterial to replace chlorine in the shelf-life extension of tilapia fillets.